New Results in an Old Framework: Comment on Samuelson and Modigliani - Pasinetti, Luigi L. (Review of Economic Studies, 1966)
Journal Article New Results in an Old Framework: Comment on Samuelson and Modigliani Get access Luigi L. Pasinetti Luigi L. Pasinetti Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 4, October 1966, Pages 303–306, https://doi.org/10.2307/2974426 Published: 01 October 1966